Kontribusi Guru Dalam Mengembangkan Minat Menghafal Alquran Di Pondok Pesantren Darullughah Wadda’wah 4 - Imaduddin; Zainal Abidin (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2022)
Jam'iyyah Busyro litahfidzil Qur'an Darullughoh Wadda`wah Islamic Boarding School 4 Bangil Pasuruan is a branch unit under the auspices of the Darullughah Wadda'wah Islamic Boarding School Foundation which was formed as a forum to accommodate and foster students who wish to memorize the Koran . The Tahfidzul Qur'an program was formed around 2004 chaired by Al-Ustadz Amin Ismail from Gresik who was a graduate student from Abuya As-Sayyid Muhammad bin Alawy Al-Maliki Al-Hasani. The purpose in writing this thesis is to want to know the teacher's contribution in developing an interest in memorizing the Koran at the tahfidzul Koran program at the Darullughah Wadda'wah Islamic Boarding School 4 Bangil, Pasuruan. The form of research used in this thesis is qualitative research, namely research that uses a natural setting, with the intention of interpreting the phenomena that occur and is carried out by involving various existing methods. The research results show that the contribution in developing interest in memorizing the Koran was made by Ustadz Amin Al-Makky as Chair of the Jam'iyyah Tahfidz Al-Quran by giving stories. The teacher's implementation in developing an interest in memorizing the Koran starts from carrying out socialization activities to the central dalwa students. Then there is giving motivation to memorize in order to foster students' interest, after that data collection is carried out for students who want to register to take part in the tahfidz program.